Extraction of Zn (II) and Cu (II) Ions Using PEG (300) - KCl Salt Aqueous Two-Phase Systems - Ammar, Saad H.; Abdul-Nabi, Waqar Abdul-Wahid; Rasheed, Musaab Khadem (Al-Khwarizmi Engineering Journal, 2011)
In this paper the process of metal ions extraction (Zn(II) and Cu(II)) was studied in PEG-KCl aqueous two phase system was investigated without using an extracting agent. The experimental runs were performance at constant temperature (25 oC), constant mixing time (30 min), and constant PH of the solution (about 3). The effect of KCl salt concentration (from 10% to 25%), volumetric phase ratio of PEG solution to KCl solution (from 0.5 to 2), and the initial metal ion concentration (from 0.25 ml to 2 ml of 1 gm/L solution) were investigated on the percent extraction of Zn(II) and Cu(II). The results indicated that the percent extraction of metal ions increase with increasing of salt concentration and phase ratio, and slightly decrease with increasing of initial metal ion concentration.